Policies to promote research and innovation in developing countries' Universities: The case of Thailand - Tantanee, Sarintip et al (Indian Journal of Public Administration)
Research and Innovation (R&I) has played an important role in constructing new knowledge in higher education institutions (HEIs) worldwide. There are both enabler and barrier factors on R&I capabilities in HEIs; therefore, this paper aims to investigate the importance, current contexts and gaps in R&I capacity building of Thai HEIs and the possibilities for improvement. Thirteen policymakers from HEI$1 (Bs Authorities and Research Funding Agencies were interviewed in-depth. In addition, an online survey has been conducted with 172 university academic staff, who have been involved in R&I. The results show that the majority of respondents agree that R&I is very important; however, these activities have not been clearly supported by national policies. From the suggestions for improvement, the whole R&I supporting system, from the national to the HEIs levels, should be developed and improved through policy, skill acquisition and job opportunities, research grants and enhancing national and international collaborations. - Reproduced.s
Keywords: Research and innovation